Collagenase injections for Dupuytren's contracture: prospective cohort study in a public health setting. Issue 5 (26th January 2019) - Fletcher, Jason; Tan, Ezekiel S. L.; Thomas, Michael; Taylor, Fraser; Elliott, Devlin; Bindra, Randy
Abstract : Background: Dupuytren's disease causes a flexion contracture of the hand that limits hand function and reduces quality of life. Traditional management is surgical excision which is associated with potentially serious complications. A viable alternative is collagenase Clostridium histolyticum (CCH) (Xiaflex®; Pfizer Australia) which is an effective, safe, outpatient treatment that to date has no published data in the Australian public health setting. Methods: A prospective cohort, single centre study, enrolling 54 patients to treat 81 joints with CCH. Patients received a single dose to the cord followed by joint manipulation 48 h later. Primary endpoint was reduction in contracture to 0 to 5° of full extension assessed 4 weeks after injection. Secondary endpoints included range of motion, patient satisfaction and function as measured by the Southampton Dupuytren's Scoring Scheme (SDSS). Results: Primary endpoint was achieved in 48% of joints (66% metacarpophalangeal and 19% proximal interphalangeal). Mean flexion contracture improved by 40 o and 25 o for metacarpophalangeal and proximal interphalangeal joints, respectively. Mean active range of motion improved by 39 o and 18 o, respectively. At 30 days and 12 months, SDSS score demonstrated sustained improvement versus baseline (1.88 versus 8.24 P ≤ 0.0005 and 1.59 versus 8.07 P ≤ 0.0005). Sixty‐eight percent of patients were either very satisfied or satisfied at 12‐month follow‐up. Side effects of treatment were minor; with oedema and bruising the most common (87% and 85%, respectively). Conclusion: CCH injections are a viable treatment for Dupuytren's contracture in the Australian public health setting. Abstract : Collagenase Clostridium histolyticum injections are a viable alternative treatment for Dupuytren's contracture in the Australian public health setting.